Heart Development and Regeneration in Non-mammalian Model Organisms - Xia, Jianhong; Meng, Zhongxuan; Ruan, Hongyue; Yin, Wenguang; Xu, Yiming; Zhang, Tiejun (Frontiers in Cell and Developmental Biology, 2020)
Cardiovascular disease is a serious threat to human health and a leading cause of mortality worldwide. Recent years have witnessed exciting progress in the understanding of heart formation and development, enabling cardiac biologists to make significant advance in the field of therapeutic heart regeneration. Most of our understanding of heart development and regeneration, including the genes and signaling pathways, are driven by pioneering works in non-mammalian model organisms, such as fruit fly, fish, frog, and chicken. Compared to mammalian animal models, non-mammalian model organisms have special advantages in high-throughput applications such as disease modeling, drug discovery, and cardiotoxicity screening. Genetically engineered animals of cardiovascular diseases provide valuable tools to investigate the molecular and cellular mechanisms of pathogenesis and to evaluate therapeutic strategies. A large number of congenital heart diseases (CHDs) non-mammalian models have been established and tested for the genes and signaling pathways involved in the diseases. Here, we reviewed the mechanisms of heart development and regeneration revealed by these models, highlighting the advantages of non-mammalian models as tools for cardiac research. The knowledge from these animal models will facilitate therapeutic discoveries and ultimately serve to accelerate translational medicine.